The effect of long chain omega-3 polyunsaturated fatty acids on muscle mass and function in sarcopenia: A scoping systematic review and meta-analysis. (December 2021) - Bird, Julia K.; Troesch, Barbara; Warnke, Ines; Calder, Philip C.
Summary: Background & aims: Sarcopenia is characterized by the progressive loss of skeletal muscle mass and function, which reduces mobility and quality of life. Risk factors for sarcopenia include advanced age, physical inactivity, obesity, and chronic diseases such as cancer or rheumatoid arthritis. Omega-3 long chain polyunsaturated fatty acids (LC PUFAs) might be associated with a reduction in risk of sarcopenia due to their anti-inflammatory effects. Methods: We conducted a systematic review and meta-analysis to quantify the effects of omega-3 LC PUFAs on muscle mass, volume and function parameters. The National Library of Medicine's MEDLINE/PubMed database was searched on 9th October 2020 for randomized controlled trials that used omega-3 LC PUFAs as an intervention with muscle-related endpoints. A snowballing search to identify additional studies was completed on 23rd April 2021. The meta-analysis was conducted using meta-essentials worksheet 3. Bias was assessed using the Jadad scale. Results: 123 studies were identified with the systematic searches. Most studies were performed in disease populations, such as cancer or chronic obstructive pulmonary disease (COPD), or in healthy individuals after a fatiguing exercise bout. The endpoints lean body mass, skeletal muscle mass, mid-arm muscle circumference, handgrip strength, quadriceps maximal voluntary capacity (MVC), and 1-repetition maximum chest press were selected for meta-analysis based on the number of available studies; thus 66 studies were included in the quantitative synthesis. Using a random effects model and 2-tailed p-value, there was a significant relationship in favor of omega-3 LC PUFA supplementation for lean body mass (effect size 0.27, 95%CI 0.04 to 0.51), skeletal muscle mass (effect size 0.31, 95%CI 0.01 to 0.60) and quadriceps MVC (effect size 0.47, 95%CI 0.02 to 0.93). Conclusion: The results indicate that there is a positive effect of omega-3 LC PUFA supplementation on overall body muscle mass and strength. Small study size and heterogeneity limit the applicability of these findings for sarcopenia prevention. Larger trials in populations at risk of sarcopenia would strengthen the evidence base.